SAT0488 ETANERCEPT CONCENTRATION IN PATIENTS WITH JUVENILE IDIOPATHIC ARTHRITIS. (2nd June 2020) - Kärki, J.; Levälampi, T.; Vähäsalo, P.; Backström, M.; Kröger, L.; Malin, M.; Putto-Laurila, A.; Pohjankoski, H.; Kautiainen, H.; Jokiranta, T. S.; Aalto, K.
Abstract : Background: Etanercept (ETN) is the most used TNF blocker in children with JIA. There is still limited real-life data of etanercept concentrations in children, especially in association with dosing. Objectives: The aim of the study was to investigate association between ETN dosing and serum trough concentration in children with non-systemic JIA. Methods: We conducted a multicenter retrospective study of 180 Finnish JIA patients (Table 1) receiving ETN either as monotherapy or in combination with one or more DMARDs (Table 2). Prior biologicals were used by 17 % of the patients. Patients were divided into two groups, ETN started before or after one year of diagnosis (Figure 1 ). ETN concentration samples (collected 2014-2017) were analyzed using validated enzyme-linked immunosorbent assay (ELISA) in Sanquin Diagnostics, Amsterdam, the Netherlands. Results: Demographics at etanercept start and diagnoses are shown in Table 1. Duration of the treatment with ETN, ETN doses, concentrations and concomitant medications at the time of concentration measurement are shown in Table 2. Association between ETN dose and concentration is shown in Figure 1 . Those who started medication early (< 1 year from diagnosis) were younger than those who started later (Table 1) and association between ETN dose and concentration was more obvious (Figure 1 ). Conclusion: There was an association between etanercept dose used and serum trough concentration and it was more evident when medication was started early after diagnosis, when the patients were younger and BSA lower. References: [1]Kneepkens EL et al. Lower etanercept levels are associated with high disease activity in ankylosing spondylitis patients at 24 weeks of follow-up. Ann Rheum Dis 2015;74(10):1825-9. [2]Bader-Meunier B et al. Etanercept concentration and immunogenicity do not influence the response to Etanercept in patients with juvenile idiopathic arthritis. Semin Arthritis Rheum 2019;48(6):1014-1018. Disclosure of Interests: None declared